2018
DOI: 10.2135/cropsci2017.01.0048
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Meteorological Factors on Wheat and Rice Yields in China

Abstract: In this study, our primary objective was to explore the effects of meteorological change on crop yield by analyzing conditions for midseason rice (Oryza sativa L.) and winter wheat (Triticum aestivum L.) in China. We conducted a detailed exploration of the relationship between yield and meteorological factors at different growing stages; specifically, the crop yield of >2000 Chinese administrative counties from 1980 to 2012 and the day‐degree data from 2481 weather stations were carefully analyzed. We first in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Thus, precipitation and soil moisture play an important role in winter wheat production from emergence to the turning-green and jointing stages. Hence, our results demonstrate that water supply conditions during the vegetative growth phase are closely linked to winter wheat growth and yield, in agreement with previous work 5,17 .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, precipitation and soil moisture play an important role in winter wheat production from emergence to the turning-green and jointing stages. Hence, our results demonstrate that water supply conditions during the vegetative growth phase are closely linked to winter wheat growth and yield, in agreement with previous work 5,17 .…”
Section: Resultssupporting
confidence: 93%
“…Zhuang et al . 17 found that in northern China, higher temperatures during the seeding and emergence stages result in a reduced yield of winter wheat. The rate of yield decrease was about –40 kg ha −1 °C −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations